Learning Process Enhancement for Robot Behavior - Baneamoon, Saeed Mohammed; Salam, Rosalina Abdul; Talib, Abdullah Zawawi (World Academy of Science, Engineering and Technology (WASET), 2007)
Designing a simulated system and training it to optimize its tasks in simulated environment helps the designers to avoid problems that may appear when designing the system directly in real world